Digital Transformation in Antenatal Care in Indonesia: The Effectiveness of The 'Bundaqusehat' Application - Delmaifanis; Novita Rina Antarsih; Siregar, Kemal N (Universitas Airlangga, 2025)
Background: Antenatal care (ANC) is recognized as an essential component of maternal health aimed at reducing maternal and fetal morbidity and mortality. Antenatal care has undergone a digital transformation through mobile health (mHealth), but research specifically discussing mHealth solutions for antenatal care in Indonesia is still limited. Purpose: This study aims to evaluate the effectiveness of the web-based application Bundaqusehat in supporting antenatal services. Methods: The research design was a quasi-experimental pretest-posttest with a control group, and the research participants included 30 pregnant women from two Health Centers (intervention group) and one Health Center (control group). Data collection was conducted using a structured questionnaire administered before and after the intervention. Statistical analysis used the T-test, with a significance set at p < 0.05. Results: The analysis showed significant improvements in pregnant women's knowledge (p = 0.001), satisfaction (p = 0.002), attitude (p = 0.002), behavior (p = 0.001), adherence to iron tablet consumption (p = 0.030), and fetal movement monitoring (p = 0.041). The intervention group showed greater adherence to the recommended antenatal practices than the control group. Conclusion: The Bundaqusehat application demonstrates significant potential in enhancing the quality of antenatal care, highlighting the critical role of digital health solutions. Future research should focus on refining and optimizing these digital interventions to maximize their positive impact.